Direito Desportivo Constitucional: o desporto educacional como direito social - Penteado, José Tadeu Rodrigues (2016)
Sport as a phenomenon born of the individual social relations developed internationally, making the borders of countries permeable and it’s rules before organized for practice games while play, leisure, fun and competition improved structurally with the evolution of societies and were organized in a peculiar manner, as an autonomous branch of law. The development of the sport as structurally organized right occurred in Brazil with the 1988 Constitution, which states the sports law in the category of sport and leisure and social rights of citizens through formal and non-formal practices, which the state must provide. The sport education provided in the 1988 Constitution as a priority, including having allocation of public funds, had formulated, in non-compliance with the constitution, the concept by Law No. 9615, of 03/24/1998, which despite being in tune with the Statute of Children and Adolescents (L. 8069/1990), had yet failed to successfully integrate sport into child and adolescent education, with use ethical and moral values. Through the affirmation of sport education as a social right, in addition to the analysis of satisfactory experiences that educational sport produced under state sponsorship after 1988, this study seeks to identify the balance between professional and social sports, with the goal of sport education permitting full development of the individual and their upbringing into a fulfilling experience of citizenship and the practice of leisure